2008
DOI: 10.1016/j.ajog.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The first demonstration that a subset of women with hyperemesis gravidarum has abnormalities in the vestibuloocular reflex pathway

Abstract: Objective-The vestibular system is a major pathway to nausea and vomiting, and the vestibuloocular reflex (VOR) is a central component; its function can be studied using the vestibular autorotation test (VAT). We hypothesize that women with hyperemesis gravidarum (HG) may have VOR abnormalities.Study Design-Women with HG were compared to women without HG using the VAT. Horizontal and vertical VOR gains and phases were evaluated at three frequency ranges: low (2.0-3.5 Hz), medium (>3.5 -5.0 Hz), and high (>5.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Some HG patients demonstrated subclinical abnormalities in vestibuloocular reflex also postpartum [27]. This could support the hypothesis of unmasking of subclinical vestibular disorders behind some cases of HG [27,28]. We found association between NVP and both history of motion sickness and seasickness.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Some HG patients demonstrated subclinical abnormalities in vestibuloocular reflex also postpartum [27]. This could support the hypothesis of unmasking of subclinical vestibular disorders behind some cases of HG [27,28]. We found association between NVP and both history of motion sickness and seasickness.…”
Section: Discussionsupporting
confidence: 86%
“…However, Whitehead et al and Gadsby et al [25,26] found higher reported frequency of motion sickness in women with NVP. Goodwin et al [27] found in their preliminary study using vestibular autorotation test abnormalities in vestibular system in patients with HG. Some HG patients demonstrated subclinical abnormalities in vestibuloocular reflex also postpartum [27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study was part of a larger study investigating the clinical, physiological, and biochemical characteristics of women with HG and a community sample of pregnant women. 13 HG was defined as persistent vomiting unrelated to other causes that required hospitalization for treatment with intravenous fluids or parenteral nutrition. Participants were interviewed during their first trimester of pregnancy.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Currently the cause of nausea and vomiting in pregnancy is unknown although there is strong evidence linking human chorionic gonadotropin or estrogens as well as genetic susceptibility possibly mediated through the vestibuloocular reflex pathway [36,37]. While spontaneous abortion rates may not be significantly different in women with or without HG [38], it can lead to long-term effects on the patient including postpartum post-traumatic stress symptoms and difficulty producing breast milk [39], and recent research suggests it may be linked to permanent neurobehavioral abnormalities in the exposed fetus [40].…”
Section: Commentmentioning
confidence: 99%